Stability of soil bacteria in undisturbed soil and continuous maize cultivation in Northern Thailand - Arunrat, Noppol; Sansupa, Chakriya; Sereenonchai, Sukanya; Hatano, Ryusuke (Frontiers in Microbiology, 2023)
Rotational shifting cultivation (RSC) in Northern Thailand serves the dual purpose of ensuring food security and meeting economic goals through maize cultivation. However, the research question remains: Does the dynamics of soil microbial communities differ between maize monoculture and RSC fields with continuous fallow throughout the season? Therefore, the objective of this study was to investigate and compare the variation of soil bacteria communities in maize monoculture and fallow RSC fields. A continuous 5-year fallow field (undisturbed soil; CF-5Y) and a continuous 5-year maize cultivation field (M-5Y) in Mae Chaem District, Chiang Mai Province, Northern Thailand were selected due to their similarities in microclimate, topography, and the 5-year duration of different field activities. Over the span of a year, we collected soil samples from the surface layer (0-2 cm depth) at both sites. These collections occurred at three-month intervals, starting from March 2022 (summer season) and followed by June (rainy season), September (rainy season), December (winter season), and March 2023 (summer season). Soil bacterial diversity and composition were analyzed using 16S rRNA genebased metagenomic analysis. The results found that undisturbed soil over a 5-year period exhibited more stable in the richness and diversity of bacteria across seasons compared to M-5Y. Notably, fertilizer application and tillage practices in M-5Y can enhance both the diversity and richness of soil bacteria. In terms of bacterial abundance, Proteobacteria prevailed in CF-5Y, while Actinobacteria dominated in M-5Y. At the genus level, Candidatus Udaeobacter dominated during the summer and winter seasons in both CF-5Y and M-5Y sites. Interestingly, during the rainy season, the dominant genus shifted to Bacillus in both CF-5Y and M-5Y fields. The soil bacterial community in M-5Y was strongly influenced by organic matter (OM) and organic carbon (OC).In contrast, in CF-5Y, there was no correlation between soil properties and the soil bacterial community, likely due to the lower variation in soil properties across seasons. β-glucosidase was the dominant enzyme in both CF-5Y and M-5Y sites, and it showed a positive correlation with OM and OC. Further studies should continue to investigate soil bacteria dynamics, considering the changes in land management practices.